Historical trends of the professional improvement of the doctor in primary health care for the early diagnosis of alterations in oral comunication - Castillo Valdés, Leydelys; Sixto Fuentes, Sahely (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: oral communication (OC) disorders as a health problem constitute a starting point for the design of professional development of professionals working at the Primary Health Care (PHC) level.Objective: to characterize the historical tendencies of professional development of physicians in PHC for the early diagnosis of OC disorders.Methods: the dialectic method was used as the guiding method. At the theoretical level: historical-logical, analytical-synthetic and inductive-deductive. From the empirical level: documentary review.Results: as national tendencies of the professional improvement of the physician in PHC for the early diagnosis of OC alterations were found in this research: the professional improvement of the Comprehensive General Practitioner (MGI) in relation to OC disorders and their early diagnosis has not been identified as a learning need; recognition of the importance of the MGI in the early detection of OC disorders, according to national demands; and the demands of a professional improvement in relation to OC disorders that enhances the real scenarios where child care is performed and prioritizes the participation of the MGI.Conclusions: in correspondence with the international tendencies of postgraduate studies, as a strategic development instrument, the professional improvement of physicians in PHC for the early diagnosis of OC disorders shows tendencies that are oriented to the professional improvement and to the quality of life of the population.